NAVIGATING THE COMPLEX LANDSCAPE OF NEUROLOGY EDUCATION - Mohammadsaeed, Chegini; Akhmadeeva, L.R. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
A survey was conducted among foreign students at Bashkir Medical University to understand their experiences in learning Neurology using the English language in Ufa, Russia. Twelve participants answered our questions and gave their feedback about their difficulties and ways to overcome them.